The Influence of Country of Origin on Purchase Intention in The Indonesian Market Mediated by Brand Image and Attitude: A Case Study of Vivo - Frederick Wilson; Pauline H.Pattyranie Tan (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
The objectives of this study are to examine the relationship between Country of Origin and Purchase Intention, to examine the relationship between Country of Origin and Brand Image, to examine the relationship between Country of Origin and Attitude towards the Brand, to examine the relationship between Brand Image and Purchase Intention, to examine the relationship between Brand Image and Attitude towards the Brand and to examine the relationship between Attitude towards the Brand and Purchase Intention. This research is quantitative. The population in this study is all consumers of the Vivo brand. The sampling procedure used in this study is non-probability with a purposive sampling technique; the researcher will take a sample of 164 consumers who have used the Vivo brand for at least 1 year. The primary data used in this study are the results of distributing questionnaires to Vivo brand consumers. The data analysis used in this study is the structural equation model (SEM), partial least squares (PLS) using Smart PLS 4.0.